Streptomyces globosus DK15 and Streptomyces ederensis ST13 as new producers of factumycin and tetrangomycin antibiotics - Charousová,Ivana (2018)
ABSTRACT Fifty seven soil-borne actinomycete strains were assessed for the antibiotic production. Two of the most active isolates, designed as Streptomyces ST-13 and DK-15 exhibited a broad range of antimicrobial activity and therefore they were selected for HPLC fractionation against the most suppressed bacteria Staphylococcus aureus (ST-13) and Chromobacterium violaceum (DK-15). LC/MS analysis of extracts showed the presence of polyketides factumycin (DK15) and tetrangomycin (ST13). The taxonomic position of the antibiotic-producing actinomycetes was determined using a polyphasic approach. Phenotypic characterization and 16S rRNA gene sequence analysis of the isolates matched those described for members of the genus Streptomyces. DK-15 strain exhibited the highest 16S rRNA gene sequence similarity to Streptomyces globosus DSM-40815 (T) and Streptomyces toxytricini DSM-40178 (T) and ST-13 strain to Streptomyces ederensis DSM-40741 (T) and Streptomyces phaeochromogenes DSM-40073 (T). For the proper identification, MALDI-TOF/MS profile of whole-cell proteins led to the identification of S. globosus DK-15 (accession number: KX527570) and S. ederensis ST13 (accession number: KX527568). To our knowledge, there is no report about the production of these antibiotics by S.globosus and S. ederensis, thus isolates DK15 and ST13 identified as S. globosus DK-15 and S.ederensis ST-13 can be considered as new sources of these unique antibacterial metabolites.